2007
DOI: 10.1038/sj.bjc.6603918
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral CRH modulates immuno-escape of ovarian cancer cells through FasL regulation

Abstract: Although corticotropin-releasing hormone (CRH) and Fas ligand (FasL) have been documented in ovarian carcinoma, a clear association with tumour progression and immuno-escape has not been established. FasL plays an important role in promoting tumour cells' ability to counterattack immune cells. Here, we examined immunohistochemically the expression of CRH, CRHR1, CRHR2 and FasL in 47 human ovarian cancer cases. The ovarian cancer cell lines OvCa3 and A2780 were further used to test the hypothesis that CRH might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 43 publications
0
51
0
1
Order By: Relevance
“…However, the special effects of CRF family peptides on cellular apoptosis in reproductive tumors are controversial at present. Evidence indicated that CRF could inhibit human endometrial adenocarcinoma cell growth (Graziani et al 2002), while others suggested that CRF repressed apoptosis (Minas et al 2007). We previously reported that Ucn could inhibit tumor growth and angiogenesis in human cancers via CRF type 2 receptor (CRFR2; Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the special effects of CRF family peptides on cellular apoptosis in reproductive tumors are controversial at present. Evidence indicated that CRF could inhibit human endometrial adenocarcinoma cell growth (Graziani et al 2002), while others suggested that CRF repressed apoptosis (Minas et al 2007). We previously reported that Ucn could inhibit tumor growth and angiogenesis in human cancers via CRF type 2 receptor (CRFR2; Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Klimaviciute et al reported that mRNA and proteins of CRF receptors are expressed in human cervix and CRF is detected in cervical tissue, indicating that the cervix is a target for the action of CRF (27). Moreover, Minas et al observed that expression of CRF and CRF receptors detected in ovarian cancer in situ and corresponding secretion of CRF modulate survival of ovarian cancer cells (28). This evidence suggests that CRF and its receptor systems have critical functions in the regulation of cancer cell progression.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from endometrial cancer, CRH has been shown to possess growth inhibitory effects in the vast majority of tumor cells and tissues (Melzig 1994, Graziani et al 2007, Minas et al, 2007, through the activation of CRH-R1 subtype (Graziani et al, 2002, Reubi et al, 2003, Graziani et al, 2007. Putative anti-tumor effects of CRH also appear to be mediated by CRH-R2, via an indirect mechanism involving the down-regulation of vascular endothelial growth factor (VEGF), and the subsequent inhibition of tumor vascularization (Bale et al, 2002).…”
Section: Introductionmentioning
confidence: 99%